Pelaksanaan Workshop Zotero Untuk Penulisan Karya Tulis Ilmiah Mahasiswa Fakultas Teknik Universitas Negeri Makassar - Kurnia Prima Putra; Fadhlirrahman Baso; Aminuddin Bakry; Syahrul; M. Syahid Nur Wahid; Ridwan Daud Mahande; Jumadi Mabe Parenreng; Nurdin Nurdin (Sakura Digital Nusantara, 2023)
This community engagement initiative aims to conduct a workshop on Zotero for students in writing academic papers. The workshop intends to introduce the use of Zotero as a tool for managing references and compiling accurate bibliographies. The methodology employed involves an interactive workshop format consisting of presentations, practical demonstrations, and question-and-answer sessions. The expected outcome of this community engagement is to provide significant benefits to students in enhancing their skills in academic writing. By utilizing Zotero, it is anticipated that students will become more efficient in managing references, avoiding plagiarism, and creating comprehensive and accurate bibliographies. Furthermore, the workshop seeks to improve students' understanding of research ethics and the use of quality information sources. This workshop aims to cater to diverse needs in academic paper writing. Additionally, the workshop serves as a catalyst for promoting the adoption of modern technologies and tools in academic writing.